Faktor Antropometri yang Mempengaruhi Indeks Massa Tubuh pada Atlet Pencak Silat Muda: Peran Jenis Kelamin dan Somatotipe - Syifa Syihab; Muchamad Rizki Sentani; Michael C Gouveia; Mulyana Mulyana; Nuryadi Nuryadi; Cleonara Yanuar Dini (Faculty of Sport and Health Sciences, 2025)
Nutritional status is crucial for enhancing athletic performance in Pencak Silat, which demands strength and optimal body proportions. The objective of this research was to examine the influence of gender on body mass index (BMI) among young Pencak Silat athletes and to assess the impact of anthropometric variables on BMI. A total of 38 athletes were assessed for height, weight, body composition, and somatotype. The statistical analysis comprised Pearson correlation, independent t-test, one way ANOVA, and multiple linear regression. The findings indicate that there were no significant disparities in BMI between both genders (p = 0.113). Most of athletes categories as mesomorphic (57.9%), followed by ectomorphic (36.8%) and endomorphic (5.3%). Regression analysis indicates that body weight (β = 0.347; p < 0.001) exerts a substantial positive influence on BMI. In contrast, height demonstrates a significant negative influence (β = -0.247; p < 0.001). Additionally, age and gender are not significant factors towards BMI. These findings underscore the inadequacies of BMI as the exclusive measure of athletes’ nutritional status and highlight the necessity of incorporating anthropometric evaluation and somatotype profile. A multidimensional evalutions may help coaches and sport nutrisionist to design effective training and nutrition strategies for long term-athletes development (LAD).